When rape goes viral: youth and sexual assault in the digital age - Gjika, Anna (University of California Press, 2024)
"Stories of teen sexting scandals, cyberbullying, and image-based sexual abuse have become commonplace fixtures of the digital age, with many adults struggling to identify ways to monitor young people's digital engagement. In When Rape Goes Viral, Anna Gjika argues that rather than focusing on surveillance, we should examine such incidents for what they tell us about youth peer cultures and the gender norms and sexual ethics governing their interactions. Drawing from interviews with teens and high-profile cases of mediated juvenile sexual assault, Gjika exposes the deeply unequal and heteronormative power dynamics informing teens' intimate relationships and digital practices, and she critically interrogates the role of technological logics, digital cultures, and broader social values in sanctioning abuse. This book also explores the consequences of social media and digital evidence for young victim-survivors and perpetrators of sexual assault, detailing the paradoxical role of technology for social and legal responses to gender violence"--